Field method for rapid quantification of labile organic carbon in hyper-arid desert soils validated by two thermal methods. Issue 2 (5th March 2014) - Fletcher, Lauren E.; Valdivia-Silva, Julio E.; Perez-Montaño, Saul; Condori-Apaza, Renee M.; Conley, Catharine A.; Navarro-Gonzalez, Rafael; McKay, Christopher P.; Cockell, Charles; Burchell, Mark; Martins, Zita
Abstract The objective of this work was to develop a field method for the determination of labile organic carbon in hyper-arid desert soils. Industry standard methods rely on expensive analytical equipment that are not possible to take into the field, while scientific challenges require fast turn-around of large numbers of samples in order to characterize the soils throughout this region. Here we present a method utilizing acid-hydrolysis extraction of the labile fraction of organic carbon followed by potassium permanganate oxidation, which provides a quick and inexpensive approach to investigate samples in the field. Strict reagent standardization and calibration steps within this method allowed the determination of very low levels of organic carbon in hyper-arid soils, in particular, with results similar to those determined by the alternative methods of Calcination and Pyrolysis–Gas Chromatography–Mass Spectrometry. Field testing of this protocol increased the understanding of the role of organic materials in hyper-arid environments and allowed real-time, strategic decision making for planning for more detailed laboratory-based analysis.